PENINGKATAN PROSES DAN HASIL BELAJAR PESERTA DIDIK DENGAN MENGGUNAKAN MODEL TEAM GAMES TOURNAMENT PADA PELAJARAN PENDIDIKAN PANCASILA DI KELAS VA SDIT AL-AKHYAR - Dian Maretha; Abdulah; Iri hamzah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study is motivated by the low learning process and outcomes of students in class V A at SDIT Al-Akhyar, as seen from the average scores of the students’ Final Exams. The purpose of this research is to identify improvements in the learning process and outcomes of students through the application of the Team Games Tournament (TGT) model in Pancasila Education lessons.The research method used is Classroom Action Research (CAR). This study was carried out in two cycles, each consisting of planning, action implementation, observation, and reflection. The subjects of this study were 19 students of Class V A at SDIT Al-Akhyar. Data collection used in this research included both qualitative and quantitative data. Qualitative data consisted of teacher and student observation sheets, while quantitative data consisted of: (1) the percentage results obtained from Yes and No answers in observation sheets, and (2) test scores given in each cycle.The results obtained from the study include: 1) an increase in the learning process using the TGT model in Pancasila Education lessons from 58% in cycle I to 79% in cycle II, 2) student learning outcomes in Pancasila Education improved each cycle after the application of the TGT model. The learning outcomes reaching the Minimum Completeness Criteria (KKTP) were 47% in cycle I and increased to 79% in cycle II.Based on the results of the research conducted, there was an improvement in the learning process and outcomes in class V A at SDIT Al-Akhyar through the application of the TGT model in Pancasila Education lessons.